Pengaruh Kepuasan Kerja, Lingkungan Kerja, dan Gaya Kepemimpinan Terhadap Kinerja Karyawan di PR. Alaina Fajar Berlian Tulungagung - Rena Anjani; Mawar Ratih K; Aprilia Dian Evasari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This Study aims to explain and test the hypothesis regarding yhe influence of job satisfaction, work environment, and leadership style on the performance of PR. Alaina Fajar Berlian Tulungagung. This study is a descriptive study with a quantitative approach, using nonprobability techniques with a purposive sampling method. The population in this study was 627 employes, with a sample of 87 employes. Data analysis techniques used include validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, t tests (partial),F tets (simultaneous), and coefficients of determination (R2), which are processed using SPSS version 23. Based on the results of the study, it can be concluded that partially the job satisfaction variable does not have a significant effect on employe performance, with a significant value of 0,060 > 0,05 and a tcount value < ttable of 1,904 < 1,998. The work environment variable does not have a partial significant effect on employe performance, with a significant value of 0,,604 > 0,05 and a tcount value < ttable of 0,520 < 1.998. The leadership style variable does not have a partial significant effect on employe performance, with a significant value of 0,262 > 0,05 with a tcount < ttable of 1,129 < 1,998. Simultaneously, the variables of job satisfaction, work environment, and leadership style do not have a significant effect on employe performance at PR. Alaina Fajar Berlian Tulungagung, with a significant value of 0,084 > 0,05 with a Fcount value < Ftable of 2,297 < 2,215. This, job satisfaction, work environment, and leadership style do not significantly affect the performance of employe PR. Alaina Fajar Berlian Tulungagung. This shows that the hypothesis Ho is accepted and Ha is rejected.